Intra- and interspecific variation in self-control capacities of parrots in a delay of gratification task - Brucks, Désirée; Petelle, Matthew; Baldoni, Cecilia; Krasheninnikova, Anastasia; Rovegno, Eleonora; von Bayern, Auguste M. P. (Animal cognition, 2022)
Forgoing immediate satisfaction for higher pay-offs in the future (delayed gratification) could be adaptive in situations that wild animals may encounter. To explain species-differences in self-control, hypotheses based on social complexity, feeding ecology, brain size and metabolic rate have been proposed. To explore these hypotheses in a comparative setting, we tested three macaw species (neotropical parrots)—great green macaws ( N = 8), blue-throated macaws ( N = 6), blue-headed macaws ( N = 6)—and the distantly related African grey parrots (afrotropical parrots; N = 8) in a modified rotating tray task, in which subjects are required to inhibit consuming a constantly available low-quality reward in favour of a high-quality reward that becomes available only after an increasing delay (min. 5 s, max. 60 s). All four species successfully waited for a minimum of 8.3 s ± 11.7 s (group level mean ± SD) with African greys reaching a delay of 29.4 ± 15.2 s, and great green macaws—as best performing macaw species—tolerating delays of 20 s ± 8 s. The best performing African grey individual reached a maximum delay of 50 s, whereas, a great green and a blue-throated macaw tolerated a delay of 30 s max. Females tolerated higher maximum delays than males. Engaging in distraction behaviours enhanced waiting performance across species and all birds were able to anticipate the waiting duration. Our results suggest that both feeding and socio-ecological complexity may be a factor in self-control, but further systematically collected comparative data on self-control of different (parrot) species are required to test the evolutionary hypotheses rigorously.